Adoption of Digital Innovation in Public Service Evaluation: Application of SuKma e Jatim in the Public Service Mall of Bojonegoro Regency - Mita Alfiatus Sa'adah; Esa Septian; Sri Kasiami (Mahesa Research Center, 2026)
The use of digital innovation in evaluating public services is crucial to improve transparency, data accuracy, and service quality in line with community needs. However, there is a gap between innovation adoption theory and field practice, particularly in terms of low user participation and suboptimal survey results. This study analyzes the adoption of the SuKma e Jatim application at the Bojonegoro regency public service mall using Rogers’ innovation diffusion theory. The method employed is qualitative, utilizing a case study approach that involves observation, in-depth interviews, and documentation techniques. The data are then analyzed using the Miles & Huberman model, with assistance from NVivo 12 software. The results show the SuKma e Jatim application has relative advantages in the form of a faster, more efficient, and more transparent evaluation process, but its compatibility and ease of use are still influenced by digital literacy and the need for technical assistance. The trial rates low due to a lack of socialization, while observability is high because survey results can be accessed in real-time and used to improve services. This study concludes that SuKma e Jatim has strong potential as a digital innovation in public service evaluation, but its successful adoption requires strengthening socialization, increasing user capacity, and continuous technical development.